Democratic Institutions and Environmental Quality: Effects and Transmission Channels - Somlanare Romuald Kinda (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
This paper aims at analysing the effect of democratic institutions on environmental quality (carbon dioxide per capita, sulfure dioxide per capita) and at identifying potential channel transmissions. We use panel data from 1960 to 2008 in 122 developing and developed countries and modern econometric methods. The results are as follows: Firstly, we show that democratic institutions have opposite effects on environment quality: a positive direct effect on environment quality and a negative indirect effect through investments and income inequality. Indeed, democratic institutions attract investments that hurt environment quality. Moreover, as democratic institutions reduce income inequality, they also damage environment. Secondly, we find that the direct negative effect of democratic institutions is higher for local pollutant (SO2) than for global pollutant (CO2). Thirdly, the nature of democratic institutions (presidential, parliamentary) is not conducive to environmental quality. Fourtly, results suggest that the direct positive effect of democratic institutions on environment quality is higher in developed countries than in developing countries. Thus, the democratic process in the first group of countries has increased their awareness for the environment protection.
Keywords: O43; Q53; C23; D31; E22; 330; Democratic institutions; Air pollution; Panel data; Income inequality; Investments